Environmental Influences on Tissue Regeneration and Repair: A Comprehensive Review - abbas, Marwa ismail; Rasool, Entissar Mansour Abdul; Mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2024)
This comprehensive review explores the influence of environmental factors on tissue regeneration and repair. The environment plays a pivotal role in the biological processes that influence the ability of tissues to recover from injury and damage. Environmental factors studied include pollution, diet, radiation exposure, and lifestyle. The review provides a detailed analysis of current studies linking these factors to the biological processes involved in tissue regeneration. It also highlights the molecular mechanisms that are affected by these factors, helping to understand how to improve treatment and rehabilitation strategies. The findings demonstrate the importance of taking environmental conditions into account when developing new methods to enhance healing. This review suggests the need for continued research in this area, with the aim of improving treatment outcomes and enhancing the quality of life for individuals with problems related to tissue repair.